2001
DOI: 10.4049/jimmunol.167.5.2469
|View full text |Cite
|
Sign up to set email alerts
|

A CD19-Dependent Signaling Pathway Regulates Autoimmunity in Lyn-Deficient Mice

Abstract: CD19 and the Src family protein tyrosine kinases (PTKs) are important regulators of intrinsic signaling thresholds in B cells. Regulation is achieved by cross-talk between Src family PTKs and CD19; Lyn is essential for CD19 phosphorylation, while CD19 establishes an Src family PTK activation loop that amplifies kinase activity. However, CD19-deficient (CD19−/−) B cells are hyporesponsive to transmembrane signals, while Lyn-deficient (Lyn−/−) B cells exhibit a hyper-responsive phenotype resulting in autoimmunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 60 publications
1
27
1
Order By: Relevance
“…Thus, the small amount of noninhibited SFK molecules seemed to be sufficient to counterbalance the barrier of intracellular phosphatase activity and trigger sufficient BCR phosphorylation to promote downstream signaling. The most plausible explanation is the existence of a positive feedback loop at the level of SFKs, possibly involving the cooperation between SFKs and Iga/Igb (59) and/or SFKs and CD19 (60,61). The existence of such a B cell-specific SFK activation feedback mechanism (absent in TCR signaling) (62) could explain the higher sensitivity of TCR signaling to the inhibition of SFKs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the small amount of noninhibited SFK molecules seemed to be sufficient to counterbalance the barrier of intracellular phosphatase activity and trigger sufficient BCR phosphorylation to promote downstream signaling. The most plausible explanation is the existence of a positive feedback loop at the level of SFKs, possibly involving the cooperation between SFKs and Iga/Igb (59) and/or SFKs and CD19 (60,61). The existence of such a B cell-specific SFK activation feedback mechanism (absent in TCR signaling) (62) could explain the higher sensitivity of TCR signaling to the inhibition of SFKs.…”
Section: Discussionmentioning
confidence: 99%
“…B cells play a major role in the development of autoimmune disease in Lyn-deficient mice. Lyn-deficient mice lacking B cells fail to develop autoimmune disease (23), as do Lyn 2/2 mice with null mutations in molecules essential for early B cell activation such as Btk and CD19 (24)(25)(26). Although few studies have investigated the role of other hematopoietic cells and the contribution of cytokines, a recent report has shown that disruption of TLR signaling in Lyn 2/2 MyD88 2/2 mice prevented the production of pathogenic auto-Abs and associated glomerulonephritis, and has suggested a role for proinflammatory cytokine secretion by dendritic cells (DCs) in disease pathogenesis (27).…”
mentioning
confidence: 99%
“…Btk activation and membrane localization requires Src family PTK and phosphatidylinositol 3-kinase (PI3-kinase) activation (10, 11, 38 -40), with Btk activation contributing to phospholipase C␥ activation and [Ca 2ϩ ] i mobilization (13,41). A major function for CD19 is the regulation of Src family PTK activity (42)(43)(44). Lyn is the primary PTK to initially phosphorylate CD19 (43), while phosphorylated CD19, in turn, amplifies Src family PTK activity through events termed "processive amplification" (27,43).…”
mentioning
confidence: 99%